2015
DOI: 10.1038/ng.3394
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of long-term gene flow and selection during domestication from analyses of Eurasian wild and domestic pig genomes

Abstract: Traditionally, the process of domestication is assumed to be initiated by humans, involve few individuals and rely on reproductive isolation between wild and domestic forms. We analyzed pig domestication using over 100 genome sequences and tested whether pig domestication followed a traditional linear model or a more complex, reticulate model. We found that the assumptions of traditional models, such as reproductive isolation and strong domestication bottlenecks, are incompatible with the genetic data. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
276
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(295 citation statements)
references
References 81 publications
16
276
0
3
Order By: Relevance
“…In agreement with other studies, for example, Frantz et al (2015), the first principal component neatly represents either the Chinese or European origin, proving that continent is the single most influential factor in explaining genetic structure of S. scrofa. Note that the international breeds, Duroc and Large White, are shifted towards Asia: a result of the well-known admixing process with Chinese pigs.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…In agreement with other studies, for example, Frantz et al (2015), the first principal component neatly represents either the Chinese or European origin, proving that continent is the single most influential factor in explaining genetic structure of S. scrofa. Note that the international breeds, Duroc and Large White, are shifted towards Asia: a result of the well-known admixing process with Chinese pigs.…”
Section: Resultssupporting
confidence: 73%
“…More recently, Frantz et al (2015) reported an analysis of 100 Asian and European complete pig genomes. They looked for potential selective signals that were shared between Asian and European populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavioral factor in selection addresses the recent hypothesis of the existence of “islands of domestication” within the genome wherein selection for desirable behavioral traits allows breeders to maintain domestic behavior within an interbred population (Frantz, 2015). Our results suggest that behavioral selection may indeed be important at the level of individual selection, but there is no evidence in this study suggesting that it can lead to hybridizing an entire population.…”
Section: Discussionmentioning
confidence: 99%
“…However, new models of domestication suggest that while spatial separation of wild and domestic types is often sought, various domestic species ranging from pigs to horses have also been cross‐bred for specific characteristics by allowing controlled introgression from wild herds. (Ottoni, 2013; Jónsson, 2014; Frantz, 2015). For most domestic breeds, this idea remains a hypothesis as the original free‐ranging wild forms have become largely extinct or restricted to a few isolated areas (Clutton‐Brock, 1987).…”
Section: Introductionmentioning
confidence: 99%